Shards of the Glass Ceiling - Svetlana Seibel (Recherches Germaniques)
Perhaps as in no other genre of literature or television, corporate conspiracy themes and corporation critique agendas abound in science fictional narratives. In television which engages the corporate machine theme, the corporation as antagonist is often fleshed out to such a degree that it becomes, for all intents and purposes, a character in the narrative. The defining traits of such an antagonist are usually projected upon, condensed and consolidated in the character of a corporate leader, a person who communicates to the audiences the essence of the corporate mindset. This article critically examines recent examples of TV series that present a tension between corporate culture, gendered notions of leadership, and posthuman subjectivity. I ask: what happens to representation when the corporate giant has a female face? It is my contention that female corporate leader characters tend to be embedded into a discourse of nurture which generates an additional moral tension in relation to the corporate machine, a tension which is uncommon for male characters of the same order but almost omnipresent in women characters. Female leadership in resistance against the corporate agenda, on the other hand, often intersects with discourses on posthuman subjectivity within which such characters unfold their critical potential most fully. This article explores such themes in two post-2000 SF TV shows – Orphan Black and Dollhouse.